A novel measurement method of a single dust particle permittivity at a microwave frequency band as I/P to accurate scattering computations: part 1 - Bashir, Saad Osman; McEwan, N.J (Allerton Press, Inc., 2012)
In electromagnetic scattering computation the scattering properties of a single particle can be evaluated if the solid permittivity of its constituent material is known. If the material is not homogeneous (e.g. water layer on the particle surface) both the structure and the permittivity of different parts must be known. However, it is possible (at least at microwave frequencies) to define an equivalent homogeneous permittivity which would produce the same scattering properties for a homogeneous particle of the same outer shape as the real one. In this work a novel measurement method of a single particle scattering for evaluating the dielectric properties of dust is derived. Results are compared with another work on bulk/scaled measurement (Part II) of dust permittivity at the same frequency band (X-band) gave matched results.